Modeling of plasma distortions by laser-induced ablation spectroscopy (LIAS) and implications for the interpretation of LIAS measurements. (24th September 2015) - Tokar, M.Z.; Gierse, N.; Philipps, V.; Samm, U.
Abstract: For the interpretation of the line radiation observed from laser induced ablation spectroscopy (LIAS) such parameters as the density and temperature of electrons within very compact clouds of atoms and singly charged ions of ablated material have to be known. Compared to the local plasma conditions prior to the laser pulse, these can be strongly changed during LIAS since new electrons are generated by the ionisation of particles ejected from the irradiated target. Because of their transience and spatial inhomogeneity it is technically difficult to measure disturbances induced in the plasma by LIAS. To overcome this uncertainty a numerical model has been elaborated, providing a self-consistent description for the spreading of ablated particles and accompanying modifications in the plasma. The results of calculations for LIAS performed on carbon-containing targets in Ohmic and additionally heated discharges in the tokamak TEXTOR are presented. Due to the increase in the electron density the 'ionisation per photon' ratio, S/XB factor, is significantly enhanced compared to unperturbed plasma conditions. The impact of the amount of material ablated and of the plasma conditions before LIAS on the level of the S/XB-enhancement is investigated.